Structural vibration for robotic communication and sensing on one-dimensional structures. - Hill, Lloyd.; Mekdara, Jerry.; Trimmer, Barry.; White, Robert D. (Tufts University. Tisch Library., 2018)
In this paper, structure-borne vibrations in a one-dimensional structure are examined as a means of communication and sensing for networks of robots. The concept is inspired by the observation that insects may use structural vibrations to communicate and to detect features of their environment. A 12 × 5 × 6 cm mobile robot capable of traversing an acoustically favorable structure is presented. A technique for measuring distance between robots and communicating commands to robots using vibrations generated on a common one-dimensional substrate are presented, and demonstrated through preliminary experimental results. Design considerations for this type of system are also discussed. © 2015 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.